Intranodal lymphangiography combined with foam sclerotherapy embolization of thoracic duct in the treatment of postoperative chylous leakage for thyroid carcinoma: a case report and review - Liu, RuiJiang; Cao, Lei; Du, JingXin; Xie, Ping (Frontiers in Radiology, 2024)
Background Chylous leakage (CL) is a rare but significant complication following cervical lymph node dissection, particularly in patients with papillary thyroid carcinoma (PTC). This condition is characterized by the leakage of lymphatic fluid, which can result in severe consequences such as malnutrition, immunosuppression, and prolonged hospital stays. Conventional treatments for CL include conservative measures and surgical interventions, but these approaches often face limitations and challenges. This case report discusses a successful treatment of CL using thoracic duct lymphangiography combined with local injection of sclerotherapy, demonstrating a novel and effective approach for managing this complication. Case presentation A 72-year-old female patient with PTC underwent total thyroidectomy and bilateral Level VI and left Levels II, III, IV, and V cervical lymph node dissection. Postoperatively, the patient developed milky drainage indicative of CL. Despite initial conservative treatments including pressure bandaging, negative pressure drainage, and nutritional adjustments, the patient's condition did not improve. The patient declined surgical options, leading to the decision to perform thoracic duct lymphangiography combined with local injection of sclerotherapy. Under real-time ultrasound guidance, the inguinal lymph nodes were accessed, and lipiodol was injected to visualize the thoracic duct. Subsequently, foam sclerosant was injected at the leakage site under fluoroscopic guidance. The procedure resulted in a significant reduction of chyle leakage, and the patient was discharged with no recurrence during a 1-year follow-up. Conclusions This case illustrates that thoracic duct angiography combined with local injection of sclerotherapy can be an effective treatment for high-output CL when conservative measures fail and surgical intervention is not preferred. The approach offers a minimally invasive alternative that can reduce complications and improve patient outcomes. The successful management of CL in this case underscores the potential of advanced interventional techniques in treating lymphatic system complications and highlights the need for further research to establish standardized treatment protocols.